The Synergy of Humanistic and Transformational Leadership in Building Adaptability and Digital Competence of Civil Servants - Diyah Nining Karniawati; Asrin Styaningrum (Proceeding of The International Conference on Business and Economics, 2026)
The purpose of this study is to analyze the synergy of humanistic and transformational leadership in building adaptability and digital competence of civil servants in the era of digital transformation. The research uses a narrative literature review approach by analyzing various literature from leading academic databases. The findings indicate that humanistic leadership creates a psychological foundation through empathy, respect for individual dignity, and psychological safety that facilitates civil servants to adapt to change without fear of failure. Meanwhile, transformational leadership acts as a catalyst by providing inspirational vision, intellectual stimulation, and motivation to master digital competencies. The synergy of these two leadership styles creates a holistic development ecosystem: humanistic leadership provides psychological safety to take learning risks, while transformational leadership provides energy and direction for continuous innovation. The theoretical implications of this research enrich the treasury of leadership theory in the context of public bureaucracy by identifying the complementary mechanisms of both leadership styles. Practical implications provide guidance for agency leaders to integrate humanistic values and transformational approaches in HR development programs to prepare civil servants who are resilient, adaptive, and digitally competent in facing the challenges of technological disruption and increasingly complex public service demands in the Society 5.0 era.